Peran Guru Dalam Mengembangkan Budaya Membaca Di Sekolah Dasar - Dewi sapira (Prodi PGSD Unsultra, 2023)
The role of teachers in fostering a reading culture in primary schools is crucial in shaping sustainable literacy habits. A strong reading culture helps students develop cognitive, language, and social skills. In the context of education in Indonesia, teachers play a strategic role as facilitators, role models, and motivators for students to love reading. This study aims to explore the role of teachers in promoting students' reading interest in primary schools and identify effective strategies that can be applied. This research uses a qualitative method with a case study approach involving interviews and observations in several primary schools. The results show that the active role of teachers is crucial in the success of developing a reading culture in schools.